Acute effects of 1-octen-3-ol, a microbial volatile organic compound (MVOC)—An experimental study - Wålinder, Robert; Ernstgård, Lena; Norbäck, Dan; Wieslander, Gunilla; Johanson, Gunnar (Toxicology letters, 2008)
Acute effects were assessed from exposure to a common volatile compound of microbial origin, the aliphatic alcohol 1-octen 3-ol (octenol). Twenty-nine volunteers performed symptom reports, measurement of blink frequency by electromyography, measurement of the eye break-up time, vital staining of the eye, nasal lavage, acoustic rhinometry, transfer tests and dynamic spirometry. Subjects were during 2 h in random order exposed to either 10 mg/m 3 of octenol or clean air as control. During octenol exposure subjective ratings of smell and nasal irritation were increased together with higher nasal lavage biomarker levels of eosinophil cationic protein, myeloperoxidase and lysozyme. Also eye irritation and blinking frequency were increased together with throat irritation, mild dyspnoea after 1-h but not after 2-h, and a small decrease in vital capacity. Ratings of headache and nausea were also increased. Atopics did not have more reactions due to exposure, whereas females experienced more smell and mucosal irritation. Thus, there were both subjective and objective signs of mild mucosal irritation of eyes and airways together with symptoms of headache and nausea.